A Leptospirosis Case Presenting with Thrombotic Thrombocytopenic Purpura - Köse Şükran; Bengü Tatar; Gürsel Ersan; Selim Topaloğlu (Balkan Medical Journal, 2013)
Background: Leptospirosis is a zoonotic disease caused by spirochetes of the genus Leptospira. While the majority of leptospirosis cases occur in the tropics, some cases are also observed in temperate regions of developing countries. The disease has various clinical presentations ranging from a mild influenza-like form to a severe potentially fatal illness accompanied by multi-organ failure. However, atypical presentations of leptospirosis have occasionally been described. Here, a case of leptospirosis presenting as thrombotic thrombocytopenic purpura (TTP) is reported.